Understanding English Minimal Pairs of Vowel - Yani Lubis; Afrohul Fadhillah Batubara; Jihan Aldie Fathani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research explores the importance of studying English minimal pairs of vowels and their impact on language learners' pronunciation skills. The discussion highlights the significance of differentiating vowel sounds through the analysis of minimal pairs, which consist of words sharing consonant sounds but differing in vowel articulation. By focusing on specific minimal pairs such as [iː] / [ɪ], [æ] / [ʌ], [ɑ:] / [ɔ], [ɛ], and [ɒ], learners can refine their ability to recognize and produce the distinct vowel sounds accurately. Mastering these minimal pairs enhances phonemic awareness, enabling learners to differentiate between similar vowel sounds, thereby improving overall pronunciation accuracy. Furthermore, the study of minimal pairs contributes to word differentiation, listening skills, and spelling and reading proficiency. It empowers learners to grasp the subtle nuances in vowel pronunciation, thereby enhancing their ability to comprehend and communicate effectively in English. In conclusion, a comprehensive understanding and application of English minimal pairs of vowels are vital for language learners striving to achieve optimal pronunciation proficiency. English minimal pairs of vowel